Removal of Reactive Dye from Aqueous Solution Using Coagulation–Flocculation Coupled with Adsorption on Papaya Leaf - Mukhlish, M. Zobayer; Khan, Maksudur R.; Islam, A.R.; Akanda, A.N.M.S. (Faculty Mechanical Engineering, UMP, 2016)
Attempts were made to investigate the effectiveness of a combined process of coagulation–flocculation and adsorption for the removal of reactive dye (Reactive Red 3BS) from aqueous solution. The effluent obtained from the coagulation–flocculation process was the raw solution for the second step of the coupling process, i.e. adsorption. The coagulation–flocculation process and the adsorption method were also studied individually. The optimum pH and the optimum dosages of alum and calcium oxide for the coagulation–flocculation process were determined. Aluminium sulphate (alum), calcium oxide and papaya leaf were used as the coagulant, coagulant aid and adsorbent, respectively. Complete dye removal from raw solution having a concentration of 100 mg L-1 could be achieved by using 300 mg L-1 of alum, 80 mg L-1 of calcium oxide and 0.20 g of papaya leaf adsorbent. Adsorption tests showed that papaya leaf could be used as a potential adsorbent for the removal of Reactive Red 3BS from aqueous solution. Themaximum sorption capacities of papaya leaf in the case of sorption from pretreated solution and pure solution were 50.23 mg g-1 and 21 mg g-1, respectively. The combined coagulation–flocculation/adsorption process may be a useful treatment technique for wastewater contaminated with reactive dye.